Do Agroforestry Systems Provide Incentives for Conservation? The Case of Makiling Forest Reserve in the Philippines - Francisco, Herminia A. (Indian Journal of Agroforestry, 2020)
To answer the question posed regarding the adequacy of the income from the agroforestry system to meet the daily expenditures of the households inhabiting the forest land, the answer is a big yes. While the study has shown that there are stages in one’s life cycle where the agroforestry system will not be sufficient to totally meet the household requirements, there are savings that could be made in earlier stages of the life cycle from the agroforestry systems, in particular, the savings to be made at two stages in the life cycle (beginning and contraction) can be used to tide over the expected deficiency in the other stages of the life cycle.Â Many studies have also shown that not everybody in the farm household could be expected to work in farming. Earlier studies in MFR specifically showed that only around 50% of the household income is obtained from farming; the rest of the income is earned from non-farm and off-farm activities. The analysis thus has shown that the agroforestry systems in MFR, especially the 2ha AF1 module, can provide sufficient income for the people to engage in this activity. Â The current average size of about two hectares appear to be an adequate farm size for the farm households. There are of course those households who own more than this size and also those who earned less than this allocation-there is thus some room for redistribution to the extent that this is possible. Will having the two-hectare farm size devoted to agroforestry system lead to resource conservation? There are evidences to show that the farming households in MFR are cooperative to the University’s efforts to protect the remaining forest cover. An interview with the key informants speak of the positive attitude of the people towards the resource which to them is big provider of their income. The general preference of the people to invest in agroforestry systems comprising mostly of perennials speak of the long term plan of the people of depend on this source of income and also of their long term commitment to protect the resource.